Islam Kafe Vs Islam Kafah: Ekspresi Memaknai Islam dalam Ruang Publik di Kalangan Milenial (Studi Kasus di Sumenep, Madura) - Damanhuri Damanhuri (Journal on Education, 2025)
This article seeks to describe the meaning of Islam by millennials in the public sphere, by focusing on three things, they are how the emergence, response, and resilience of millennials in expressing their Islam in public cafes and mosques. By using a qualitative approach, recollecting data were based on observations, interviews with managers and staff/follower as well as important documents. This data, then, is analyzed critically and descriptively. This study obtains two main findings. First, Islamic expressions in public cafes caused the problem of market-oriented economic capitalism and not educating for the benefit wider community, so managers try to raise capital through investment from pesantren alumni as an economic and social modality as well as by offering a menu of sorogan kitab (pesantren book), selawatan, and scientific activities as priority marketing to attract consumers. This strategy is also resilient in strengthening the company profile of the cafe. Second, the expression of Islam in the mosque is aimed at reviving the house of God, takmir joint with national ustadz (preacher) such as UAS, Sugik Nur, and Hanan Attaki to recruit worshipers as well as to introduce Islam more radically to urban communities. Islamic learning focused on faith and ubudiyah holding on routinely after maghrib and subuh prayer, and "sajadah fajar" (down mat) program for shaping other mosques the same as theirs.